Human Development and related Components with Malnutrition in Children: a Global Ecological Study - Mokhtar Soheylizad (International Journal of Pediatrics, 2016)
Background: It is necessary to get information on nutrition situation in children and epidemiology of the malnutrition to use for planning and health policy making, therefore this study aimed to identify the role of human development on nutrition situation in children under-five years of old worldwide.Methods: This ecological study was performed on the relation of the nutrition situation of children under 5 years of old and HDI. Data about the HDI and other indices were obtained from the UNDP database and Data about prevalence of wasting, stunting and overweight in children under 5 (%) were obtained from WHO. Correlation bivariate method were used to assessment of the correlation between the prevalence of nutrition status and the HDI.Results: Globally mean prevalence of stunting, wasting and overweight were 23.4, 6.2 and 7.1 percent respectively. There was a negative significant correlation between prevalence of stunting and wasting with HDI, Life expectancy at birth, Mean year of schooling, Physician per population, maternal mortality rate (MMR) and Gross national income (P